Heart and Cardiac Substructure Dose Sparing in Synchronous Bilateral Breast Radiotherapy: A Dosimetric Study of Proton and Photon Radiation Therapy - Sun, Tao; Lin, Xiutong; Tong, Ying; Liu, Xiao; Pan, Lingjing; Tao, Cheng; Duan, Jinghao; Yin, Yong (Frontiers in Oncology, 2020)
Background: Synchronous bilateral breast cancer is rare. The purpose of this study was to compare the dosimetric differences in intensity-modulated radiation therapy (IMRT), volumetric-modulated arc therapy (VMAT), helical tomotherapy (HT) and intensity-modulated proton therapy (IMPT) and to find an optimal radiotherapy technique for bilateral breast cancer radiotherapy. Methods: For 11 patients who received synchronous bilateral whole-breast irradiation without local lymph nodal regions, six plans were designed for each patient: IMRT with a single isocenter (IMRT-ISO1), IMRT with two isocenters (IMRT-ISO2), VMAT with a single isocenter (VMAT-ISO1), VMAT with two isocenters (VMAT-ISO2), HT, and IMPT. The differences between the single- and dual-isocentric plans for IMRT and VMAT were compared, and the plan with the better quality was selected for further dosimetric comparisons with IMPT and HT. The plan aimed for a target coverage of at least 95% with the prescription dose of 50 Gy (relative biological effectiveness, RBE), while minimizing the dose of organs at risk. Results: IMRT-ISO1 and VMAT-ISO2 plans were adopted for further dosimetric comparisons because of the reduced dose of the heart and/or lungs compared to IMRT-ISO2 and VMAT-ISO1 plans. The dose coverage of the PTV was significantly higher in IMPT plans than in all other plans. VMAT and IMPT plans showed the best conformity, whereas IMRT plans showed the worst conformity. Compared to IMRT and VMAT plans, IMPT and HT plans achieved significantly higher dose homogeneity. IMPT plans reduced the mean dose and low dose volume (V5, V10, and V20) of the heart, left anterior descending artery (LAD) and left ventricle (LV). In high-dose volumes of the heart and cardiac substructures, the IMPT, VMAT and HT techniques showed similar advantages, and IMRT plans increased the values more than other techniques. IMPT plans had the maximal lung and normal tissue sparing but increased the skin dose compared to IMRT and VMAT plans. Conclusions: IMPT plans improve both the target coverage and the OAR sparing, especially for the heart, cardiac substructures (LAD and LV), lungs and normal tissue, in synchronous bilateral breast radiotherapy. VMAT and helical tomotherapy could be selected as suboptimal techniques for SBBC patients.